2003
DOI: 10.1007/s11881-003-0004-6
|View full text |Cite
|
Sign up to set email alerts
|

Matthew effects in children with learning disabilities: Development of reading, IQ, and psychosocial problems from grade 2 to grade 8

Abstract: Reading achievement, IQ, and behavior problems were assessed in second and eighth grade for a longitudinal sample of 57 children. Changes in these scores over time were compared for children with no learning disabilities versus children with math or reading disabilities (research-identified and~or school-identified). A widening of the group difference in IQ was seen between the math disabled and nondisabled groups, but otherwise the gaps between groups remained unchanged or narrowed over the six-year interval,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
86
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 44 publications
11
86
1
4
Order By: Relevance
“…Other predictions of the model have also been tested, with similarly equivocal results (Pfost et al, 2014). Some studies report data that support a Matthew effect for reading ability (Juel, 1988), but others report a stable achievement pattern (Aarnoutse & van Leeuwe, 2000;Catts, Adlof, & Fey, 2003;Scarborough & Parker, 2003;Shaywitz et al, 1995) or a compensatory effect (Parrila, Auonola, Leskinen, Nurmi, & Kirby, 2005;Shaywitz et al, 1995). The diversity of findings in these studies is undoubtedly related to the wide variety of outcome variables and ages of readers as well as to the characteristics of the sample group and study methodologies.…”
Section: The Existence Of a Matthew Effect For Vocabularymentioning
confidence: 99%
See 1 more Smart Citation
“…Other predictions of the model have also been tested, with similarly equivocal results (Pfost et al, 2014). Some studies report data that support a Matthew effect for reading ability (Juel, 1988), but others report a stable achievement pattern (Aarnoutse & van Leeuwe, 2000;Catts, Adlof, & Fey, 2003;Scarborough & Parker, 2003;Shaywitz et al, 1995) or a compensatory effect (Parrila, Auonola, Leskinen, Nurmi, & Kirby, 2005;Shaywitz et al, 1995). The diversity of findings in these studies is undoubtedly related to the wide variety of outcome variables and ages of readers as well as to the characteristics of the sample group and study methodologies.…”
Section: The Existence Of a Matthew Effect For Vocabularymentioning
confidence: 99%
“…As a final consideration, the populations studied may have differed in amount or kind of intervention received. Hence, although the Matthew effect model has been a very helpful framework for researchers, educators, and clinicians alike, evidence for it has remained elusive (Pfost et al, 2014;Scarborough & Parker, 2003).…”
Section: The Existence Of a Matthew Effect For Vocabularymentioning
confidence: 99%
“…Although this effect has often been noted, few studies have tested the hypothesis directly (Bast & Reitsma, 1998). Furthermore, not all studies have observed the effect (e.g., Scarborough & Parker, 2003;Shaywitz et al, 1999;Shaywitz, Holford et al, 1995), nor has it been found for all aspects of reading (Bast & Reitsma, 1998).…”
Section: Stability Of Reading Ability and Disabilitymentioning
confidence: 99%
“…In another vein, researchers (Langer, 1986a,b;Chall & Jacobs, 1983) argued that reading, writing, and intelligence are unconnected given the assumption that complexities in reading and writing are a result of a form of highly restricted cognitive discrepancy, which may not affect children's intelligence quotient (IQ). Briggs et al (2014), Gustafson and Samuelsson (1999), and Scarborough and Parker (2003) criticized this view by arguing that reading and writing difficulties restrict children's intelligence in many cognitive domains (e.g., debate, describing, discussion, reading, knowing, labelling, summarising, translating, and vocabulary).…”
Section: Introductionmentioning
confidence: 99%